Impact of probiotics, prebiotics, and synbiotics on digestive enzymes, oxidative stress, and antioxidant defense in fish farming: current insights and future perspectives - Amenyogbe, Eric; Droepenu, Eric Kwabena; Ayisi, Christian Larbi; Boamah, Grace Afumwaa; Duker, Rahmat Quaigrane; Abarike, Emmanuel Delwin; Huang, Jian-sheng (Frontiers in Marine Science, 2024)
There has been a surge of research in the aquaculture industry investigating probiotic, prebiotic, and synbiotic interventions on the physiological mechanisms of fish, specifically digestive enzymes, oxidative stress, and antioxidant defense. In fish, probiotics have been shown to improve nutrient utilization and growth performance by stimulating digestive enzymes. Meanwhile, probiotics, prebiotics and synbiotics have also been studied for their ability to modulate oxidative stress and antioxidant defense mechanisms in fish, highlighting their multifaceted health benefits. This review identified current trends, research gaps, and future considerations in this evolving field. Although promising findings have been made, a significant research gap exists in understanding the specific role of probiotics prebiotics, and synbiotics in modulating digestive enzymes, oxidative stress, and antioxidant defense systems in a variety of fish species. As this study investigate into the existing body of literature, it becomes evident that while certain aspects of these interactions have been elucidated, a nuanced and comprehensive understanding still needs to be discovered. The variations in experimental design, species-specific responses, and the lack of standardized methodologies contribute to the complexity of the field. Digestive physiology and antioxidant defense mechanisms vary among different fish species, so future research should focus on species-specific responses to probiotic, prebiotic, and synbiotic formulations. It will also be possible to establish robust correlations between dietary interventions and observed effects through a systematic experimental design and methodology approach. Accordingly, further research is needed to understand the interactions between probiotics, prebiotics, and synbiotics in fish and digestive enzymes, oxidative stress, and antioxidant defense. Identifying research gaps and adopting standardized methodologies can help develop tailored strategies to optimize aquaculture fish health and growth performance.